Evaluation of titanium dioxide and tantalum pentoxide nanoparticles for coating NiTi archwires in orthodontics: An in vitro study - Abeer B Mahmood; Akram F Alhuwaizi; Mohammed K Khalaf; Abbas R Zaher (College of Dentistry/ University of Baghdad, 2024)
Background: This study aims to enhance the biocompatibility of Nickel-Titanium (NiTi) alloy by developing a new coating using titanium dioxide (TiO2) and titanium pentoxide (Ta2O5) through direct current (DC) reactive sputtering technology. Materials and methods: Two distinct coating materials, namely, TiO2 and Ta2O5, were used to fabricate NiTi orthodontic archwires with improved surface properties. TiO2 nanoparticles, with thickness ranging from 21.90 nm to 31.93 nm, were deposited onto NiTi alloy substrates through DC reactive sputtering deposition under different power conditions. Results: X-ray diffraction and field emission scanning electron microscopy validated the uniformity and morphology of the coatings. Immersion tests in simulated body fluid (SBF) revealed significant hydroxyapatite layer growth on TiO2-coated NiTi, especially at a sputtering power of 240 W. Reduced nickel ion release was observed on TiO2 nanoparticles with a thickness of 21.90 nm at 50 W sputtering power compared with 31.93 nm-thick nanoparticles at 240 W. Ta2O5 thin films were deposited on NiTi substrates through DC magnetron reactive sputtering at ~100 °C with a deposition power of 50 W. Structural and morphological analyses through optical microscopy and X-ray diffraction, atomic force microscopy, and scanning electron microscopy revealed the homogeneity and low roughness of the coatings. Biocompatibility assessments in artificial saliva and SBF solutions established that Ta2O5-coated NiTi alloys exhibited superior electrochemical behavior, enhanced corrosion resistance, and diminished Ni ion release compared with uncoated specimens. Conclusion: TiO2 and Ta2O5 coatings not only improved the biocompatibility of NiTi orthodontic archwires but also presented a promising path for advanced biomedical applications. These coatings have potential in improving the cellular behavior and performance of NiTi-based orthodontic devices.